Dynamic Governance Strategy in Pollution and Damage Control Patterns in the Citarum Riverside (DAS) - Neneng Zakiah; Yogi Suprayogi (Jurnal Ilmu Pemerintahan)
The pattern of pollution and damage control in the Citarum Riverside (DAS) carried out by the Regional Government of West Java Province has not been optimal because the environment and water around the river flow are still polluted for two decades. This research aimed to examine the dynamic capabilities of local governments as a positive step to restore the glory of the Citarum River. The research method used qualitative methods, data collection techniques used observation, and the data only refers to secondary data. It was conducting analysis used the Systemic Literature Review (SLR) method to map previous research and to found a novelty from this research using three databases. They were Taylor and Francis, Emerald and Science Direct. The theory was Dynamic Governance by Neo & Chen, focusing on competency dimensions of Thinking Ahead, Thinking Again, and Thinking Across. The results were whole the Regional Government of West Java Province has moved in a dynamic direction because it has created a variety of innovative policies and programs, as a form of innovation from the realization of the Thinking Ahead dimension. The establishment of a policy base related to normalization of the Citarum River consisting of presidential and governor regulations and The existence of new dynamics including the involvement of the ulemas as actors in the revitalization process of the Citarum River also take a part on it. Realization of the Thinking Again dimension, namely the running of the Citarum River normalization business programs that refer to regional policies. Then the realization of the Thinking Across dimension is the initiative of the West Java Provincial Government to adopt the pentahelix model in conducting collaborations related to the improvement of the Citarum River.